Effect of misoprostol on the pharmacokinetics of sustained release diclofenac in Myanmar healthy male volunteers - Aung, Htet Htet; Soe, Aye; Aye, Nu Nu (Siriraj Medical Journal, 2017)
Background: Sustained release diclofenac (diclofenac SR) is the commonly used non-steroidal anti-inflammatory drug for chronic inflammatory conditions such as rheumatoid arthritis.Misoprostol, prostaglandin analogue, is the agent that enhances gastrointestinal mucosal defense. Concomitant administration of misoprostol with diclofenac SR can prevent the gastrointestinal side effects of diclofenac SR. Objective: The purpose of the study was to explore the effect of misoprostol on the pharmacokinetics of diclofenac SR in healthy volunteers. Methods: Crossover study was evaluated in 14 male volunteers. Single oral dose of 100 mg diclofenac SR was concomitantly administered with 200 µg misoprostol with one-week wash out period. Plasma concentrations at 0, 0.5, 1, 1.5, 2, 3, 6 and 10 hrs were determined by high performance liquid chromatography (HPLC). Pharmacokinetic parameters such as area under concentration-time curve (AUC0-∞), peak plasma concentration (Cmax), time to achieve peak plasma concentration (Tmax), absorption half-life (T½(ab)), elimination half-life (T1/2(el)), absorption rate constant (Kab), and elimination rate constant (Kel) were determined. Results: With misoprostol, the mean AUC0-∞ of diclofenac SR was significantly reduced from 12.11±5.25µg/mL×hr to 4.17±2.72µg/mL×hr (p<0.001). The mean Cmax was also significantly decreased from 1.43±0.46 µg/mL to 0.98±0.48 µg/mL (p<0.05). The mean Tmax was decreased from 1.61±0.53hr to 1.46±0.41hr (p>0.05). The mean T½(ab) was decreased from 0.56±0.23hr to 0.54±0.19hr (p>0.05). The mean Kab were almost the same 1.43±0.54hr-1 and 1.43±0.48hr-1. The mean T1/2(el) was decreased from 3.68±1.64hr to 3.03±1.08hr (p>0.05). The mean Kel was increased from 0.21±0.09hr-1 to 0.25±0.09hr-1 (p>0.05). Conclusion: There was a significant reduction in the extent of absorption of diclofenac SR when concomitantly administered with misoprostol. Therefore, the dose of diclofenac SR may need to be increased to avoid therapeutic failure of diclofenac SR or concurrent use with misoprostol may need to be changed to other gastroprotective agents.